From genome to toxicity: a combinatory approach highlights the complexity of enterotoxin production in Bacillus cereus - Jeßberger, Nadja; Krey, Viktoria M.; Rademacher, Corinna; Böhm, Maria-Elisabeth; Mohr, Ann-Katrin; Ehling-Schulz, Monika; Scherer, Siegfried; Märtlbauer, Erwin (Frontiers in Microbiology, 2015)
In recent years Bacillus cereus has gained increasing importance as a food poisoning pathogen. It is the eponymous member of the B. cereus sensu lato group that consists of eight closely related species showing impressive diversity of their pathogenicity. The high variability of cytotoxicity and the complex regulatory network of enterotoxin expression have complicated efforts to predict the toxic potential of new B. cereus isolates. In this study, comprehensive analyses of enterotoxin gene sequences, transcription, toxin secretion and cytotoxicity were performed. For the first time, these parameters were compared in a whole set of B. cereus strains representing isolates of different origin (food or food poisoning outbreaks) and of different toxic potential (enteropathogenic and apathogenic) to elucidate potential starting points of strain-specific differential toxicity. While toxin gene sequences were highly conserved and did not allow for differentiation between high and low toxicity strains, comparison of nheB and hblD enterotoxin gene transcription and Nhe and Hbl protein titers revealed not only strain-specific differences but also incongruence between toxin gene transcripts and toxin protein levels. With one exception all strains showed comparable capability of protein secretion and so far, no secretion patterns specific for high and low toxicity strains were identified. These results indicate that enterotoxin expression is more complex than expected, possibly involving the orchestrated interplay of different transcriptional regulator proteins, as well as posttranscriptional and posttranslational regulatory mechanisms plus additional influences of environmental conditions.